Pengaruh Tari Tradisional Meningkatkan Motorik Kasar Anak 5-6 Tahun di TK IT Insan Madani (International Forum of Researchers and Lecturers, 2025)
This research aims to explore the role of traditional dance activities in developing gross motor skills of early childhood students at TK Nurul Ilmi. Utilizing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that traditional dance serves not only as a medium to improve motor coordination, balance, and agility but also fosters positive behavioral traits such as confidence, cooperation, and enthusiasm. Teachers reported that children were more motivated and engaged when physical activities were integrated with music and rhythmic movements. This study emphasizes the importance of incorporating culturally relevant activities in early childhood education to support holistic development. The research provides valuable insights for educators to develop creative learning strategies and for future studies to investigate broader cultural applications in early childhood development.